Format Methods on Storage Media (Hard Disk) for Optimization Data Storage Capacity - Saukani, Imam; Nuraini, Eko; Nurhadi, Slamet; Sumarno, Agus Sukoco Heru; Saptawati, Rina Tri Turani; Prasetyo, Prasetyo; Sifaunnufus Ms, Fi Imanur (Asian Journal Science and Engineering, 2023)
This research is to determine how much storage capacity in the File Allocation Table 16 (FAT16), File Allocation Table 32 (FAT 32) and New Technology File System (NTFS), the use of the hard drive is currently the of the maximum capacity will not be able to use when not using the appropriate partition, because it can affect the amount of storage capacity available after the hard disk in the partition. This type of research is reviewed based on its purpose of use, so the research to be conducted is applied research because the products of this research can be used by all computer users. Ultimately, the findings from this study will contribute to a comprehensive understanding of how file system selection and partitioning can influence the actual storage capacity of hard drives, thus informing best practices for maximizing available storage space. Keywords: New Technology File System, File Allocation Table, Storage Media